Development of Interactive Media Abacaga Adventure to Improve Capabilities Early Children's Beginning Reading - Sri Ismi Pebriani; Abdullah Sinring; Azizah Amal; Herlina Herlina; Rusmayadi Rusmayadi; Abdul Hakim (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aimed to identify learning needs, develop a prototype, and examine the validity, practicality, and effectiveness of the Abacaga Adventure interactive media for reading for beginners in early childhood. The ability of reading for beginners constitutes a critical dimension of children’s language development; however, instructional practice in the field continues to rely predominantly on less interactive media that are inadequately aligned with the developmental characteristics of young learners. Such conditions contribute to difficulties among children in letter recognition, syllable reading, and simple word comprehension. Consequently, the development of instructional media that is engaging, enjoyable, and accessible is essential to support the process of reading for beginners. This study employed a research and development (R&D) approach using the 4-D model, comprising four phases: define, design, develop, and disseminate. Data were collected through observation, interviews, and questionnaires. The research subjects consisted of four teachers, and data were analyzed using both qualitative and quantitative techniques. The findings reveal that the Abacaga Adventure interactive media is highly needed by teachers as an alternative instructional medium for reading for beginners. The media prototype was developed in the form of an interactive calendar encompassing sequential stages of letter introduction, syllables, words, and simple sentences, accompanied by a user guide. The result of media validation obtained a score of 82.25%, categorized as highly valid. Practicality, as assessed through the teachers’ response questionnaires obtained a score of 85.75%, classified as highly practical, while the effectiveness obtained 85.75%, categorized as highly effective. Based on the aforementioned findings, it is concluded that the Abacaga Adventure interactive media is feasible for use, as it has been demonstrated to be valid, practical, and effective in enhancing the ability of reading for beginners in early childhood.